Recent progress with next‐generation biomarkers in muscle‐invasive bladder cancer. (6th September 2016) - Contreras‐Sanz, Alberto; Roberts, Morgan E; Seiler, Roland; Black, Peter C
Abstract: Muscle‐invasive bladder cancer is a heterogeneous disease with different clinical phenotypes. Histomorphological variants, variable mutation rates and aberrant protein expression, along with the recently identified molecular subtypes, have been linked to prognosis and response to therapy. Complete response to chemotherapy and outcome after radical cystectomy are difficult to predict. To date, no validated pathological or clinical test exists to predict response. Advances in high‐throughput, next‐generation, genomic techniques to study the molecular pathways that govern the disease have led to novel strategies for the identification of such biomarkers relevant to muscle‐invasive bladder cancer. Progress has been made not only in tissue‐based biomarkers, but also in the liquid biopsy field. Liquid biopsies represent an opportunity to obtain patient samples non‐invasively at multiple time‐points during their treatment course without the need for biopsy. Especially in the metastatic setting, this will allow monitoring of the molecular evolution of the tumor under treatment, which should inform subsequent therapeutic decisions.